Bipolar hemiarthroplasty versus total hip arthroplasty in allograft-prosthesis composite reconstruction of the proximal femur following primary bone tumour resection. (April 2020) - Jamshidi, Khodamorad; Mirkazemi, Masoud; Gharedaghi, Mohammad; Izanloo, Azra; Mohammadpour, Mehdi; Pisoudeh, Karim; Bagherifard, Abolfazl; Mirzaei, Alireza
Abstract : Aims: The consensus is that bipolar hemiarthroplasty (BHA) in allograft-prosthesis composite (APC) reconstruction of the proximal femur following primary tumour resection provides more stability than total hip arthroplasty (THA). However, no comparative study has been performed. In this study, we have compared the outcome and complication rates of these two methods. Methods: In a retrospective study, 57 patients who underwent APC reconstruction of proximal femur following the primary tumour resection, either using BHA (29) or THA (28), were included. Functional outcome was assessed using the Musculoskeletal Tumour Society (MSTS) scoring system and Harris Hip Score (HHS). Postoperative complications of the two techniques were also compared. Results: The mean follow-up of the patients was 8.3 years (standard deviation (SD) 5.5) in the BHA and 6.9 years (SD 4.7) in the THA group. The mean HHS was 65 (SD 16.6) in the BHA group and 88 (SD 11.9) in the THA group (p = 0.036). The mean MSTS score of the patients was 73.3% (SD 16.1%) in the BHA and 86.7% (SD 12.2%) in the THA group (p = 0.041). Limping was recorded in 19 patients (65.5%) of the BHA group and five patients (17.8%) of the THA group (p < 0.001). Dislocation occurred in three patients (10.3%) of the BHA group and two patients (7.1%) of the THA group. Conclusion: While the dislocation rate was not higher in THA than with BHA, the functional outcome was significantly superior. Based on our results, we recommend THA in APC reconstruction of the proximal femur. Cite this article: Bone Joint J 2020;102-B(4):524–529.